2017
DOI: 10.1111/jphp.12807
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of oleuropein and semisynthetic acetyl-derivatives determined by measuring malondialdehyde in rat brain

Abstract: Both natural and semisynthetic polyphenol derivatives from a natural source as olive leaves were able to reduce MDA detection. The more lipophilic acetyl-derivatives showed an antioxidant activity greater than parent compounds. This potency seems to put in evidence a strict correlation between lipophilicity and bioavailability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 21 publications
3
14
0
Order By: Relevance
“…Furthermore, the toxicity of pre-formed fibrils treated with the polyphenol was not significantly affected even after a prolonged treatment (5 days), yet in the presence of a significant reduction of oxidative stress. The reduced cellular levels of ROS could result from the radical scavenging properties of OleA in accordance with previous studies describing the role of the antioxidant properties of this polyphenol in the prevention of amyloid assembly cytotoxicity 70 , 71 . However, in this case, aggregate toxicity persisted because OleA failed to reduce the membrane activity of the pre-formed fibrils treated with the polyphenol.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the toxicity of pre-formed fibrils treated with the polyphenol was not significantly affected even after a prolonged treatment (5 days), yet in the presence of a significant reduction of oxidative stress. The reduced cellular levels of ROS could result from the radical scavenging properties of OleA in accordance with previous studies describing the role of the antioxidant properties of this polyphenol in the prevention of amyloid assembly cytotoxicity 70 , 71 . However, in this case, aggregate toxicity persisted because OleA failed to reduce the membrane activity of the pre-formed fibrils treated with the polyphenol.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, it should be also outlined that the ADME properties of this nutraceutical product, and consequently its biological effect in vivo, might be ascribed to the concurrent presence of all the PRES components. Finally, both oleuropein and hibiscus acid have shown interesting and promising neuroprotective effects also in in vivo models of neurodegenerative diseases [10,[40][41][42][43]. Moreover, oleuropein or its active metabolite, hydroxytyrosol, is found in a significant amount in the brain following oleuropein peripheral administration [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that lipid oxidation level decreased significantly in the samples during the cold storage period [34]. In another study investigating the antioxidant activity of natural and synthetic polyphenol derivatives in O. europea, it was determined that the antioxidant activity of lipophilic acetyl derivatives was higher [35]. In a study using a mixture of extracts obtained from O. europea leaves and Hibiscus sabdariffa flowers, the mixture was reported to show a high degree of cytoprotective and antioxidant activity on human umbilical vein endothelial (HUVECs) cells [36].…”
Section: Antioxidant Activitymentioning
confidence: 99%